2022
DOI: 10.5194/cp-18-1011-2022
|View full text |Cite
|
Sign up to set email alerts
|

Melt in the Greenland EastGRIP ice core reveals Holocene warm events

Abstract: Abstract. We present a record of melt events obtained from the East Greenland Ice Core Project (EastGRIP) ice core in central northeastern Greenland, covering the largest part of the Holocene. The data were acquired visually using an optical dark-field line scanner. We detect and describe melt layers and lenses, seen as bubble-free layers and lenses, throughout the ice above the bubble–clathrate transition. This transition is located at 1150 m depth in the EastGRIP ice core, corresponding to an age of 9720 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…Comparing our results with Westhoff et al. (2022), we determine that the SE‐Dome site is more likely to melt, and form MLs than the EGRIP in the northern GrIS.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Comparing our results with Westhoff et al. (2022), we determine that the SE‐Dome site is more likely to melt, and form MLs than the EGRIP in the northern GrIS.…”
Section: Resultssupporting
confidence: 77%
“…Westhoff et al. (2022) reported that three MLs were detected in the EGRIP ice core from 1800 to 1964, whose thicknesses are observed. The 1889 CE melt event consists of two MLs with a total of 8.5 mm thickness and the 1950 CE melt event, with a ML of 3.1 mm thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Below a depth of 1375 m (bag 2500, 14.6 ka b2k (Gerber et al, 2021)) constant settings were used. We do not investigate cloudy bands from the Holocene (Westhoff et al, 2022) and cloudy bands showing deformation features to reduce one factor of complication. Andersen et al (2006) and Winstrup et al (2012) showed that cloudy bands appear in an annual cyclicity and that a single cloudy band, i.e.…”
Section: Cloudy Band Typesmentioning
confidence: 99%
“…The principal minerals are gypsum, quartz, feldspar, and mica and mineral diversity decreases slightly with depth. However, various sulfate-minerals, such as Mg-/Na-/K-sulfates or bloedite, were found in the upper 900 m. In addition, visual stratigraphy was measured continuously on the EGRIP ice core (Westhoff et al, 2021(Westhoff et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…7c). Summer melt layers from the Agassiz Ice Cap and Greenland ice sheet provide robust records of warmer events during the Holocene (∼ 7-8 ka; Fisher et al, 1995;Westhoff et al, 2022). These warmer periods likely initiated or accelerated the ice melt when (1) a thin layer of sediments covered the ice or (2) topographic depressions allowed the accumulation of snow and water, hence overall warmer conditions, which further accelerated the melting of the buried glacier ice.…”
Section: Conceptual Model Of Thermokarst Lake Development In Ice-wedg...mentioning
confidence: 99%